Pengaruh Harga dan Kualitas Produk terhadap Keputusan Belanja Online di Kalangan Mahasiswa Program Studi Pendidikan Ekonomi - Nanlohy, Trully Filia; Louhenapessy, William George Mozes; Tupamahu, Fenri Abraham (Universitas Pattimura, 2023)
This study aims to determine the extent to which price and product quality influence students' online shopping decisions via the social media platform Facebook. In today’s digital era, consumer behavior—particularly among university students—has shifted significantly with the rise of social media as a medium for online transactions. This study employs a quantitative approach with multiple linear regression analysis to examine the relationship between the independent variables (price and product quality) and the dependent variable (purchase decision). The respondents consisted of 30 students from the Economics Education Study Program, FKIP Pattimura University, who actively shop for products via Facebook. The results indicate that price and product quality simultaneously have a significant influence on purchasing decisions. Partially, product quality exerts a more dominant influence than price. Students tend to consider durability, product conformity with descriptions, and visual appeal before making a purchase, rather than being swayed solely by low prices. This study emphasizes the importance of consumer trust in product quality within digital marketing contexts. The practical implication of this research suggests that online sellers should prioritize product quality, provide accurate information, and build positive relationships with consumers